Optimal network reconfiguration and distributed generation integration for power loss minimization and voltage profile enhancement in radial distribution system - Naresh Manandhar,; Shree Raj Shakya,; Sudip Bhattrai, (Journal of Innovations in Engineering Education, 2023)
Network Reconfiguration with Distributed Generation (DG) integration can significantly minimize the power loss and enhance the voltage profile.  This paper presents power loss minimization and voltage profile enhancement measures in radial distribution systems through optimal network reconfiguration and DG integration. Initially, the approach was tested in a standard IEEE 33-Bus system in MATLAB using the Backward/Forward Propagation Power Flow method. Voltage Stability Index (VSI) was used to determine the candidate bus to locate for DG integration. Artificial Bee Colony (ABC) algorithm was used to find the optimal solution. Six different scenarios for network reconfiguration and DG integration were analysed by using the real distribution network of the Nepal Electricity Authority (NEA), Kirtipur Distribution Center. The simulated results were compared with the base case scenario and were validated with similar results from the previous studies. Among them, Scenario VI (simultaneous network reconfiguration and DG integration) gave a most favorable result in terms of power loss minimization and voltage profile enhancement. Test results in this study show that the active power loss has reduced by 72.19% and 57.69% for IEEE 33-Bus system and NEA 63-Bus system respectively. It also showed that ABC algorithm has outperformed other popular metaheuristic algorithms.